Anodizing quality 5XXX aluminum alloy with high strength and high formability and its manufacturing method

The development of specific anodized aluminum alloys with balanced elemental compositions and advanced processing methods achieves high strength, excellent anodizing quality, and high formability, overcoming the mechanical damage susceptibility and strength-anodizing quality trade-offs in existing alloys.

JP7649733B2Active Publication Date: 2025-03-21NOVELIS INC(US)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021196927
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-04-05
Filing Date
2021-12-03
Publication Date
2025-03-21
Estimated Expiration
2038-04-04

AI Technical Summary

Technical Problem

Current anodized quality 5xxx series aluminum alloys have yield strengths typically in the range of 170MPa to 190MPa, making products susceptible to mechanical damage such as scratching, denting, or bending, and increasing strength often deteriorates anodizing quality.

Method used

Development of anodized aluminum alloys with specific compositions, including 0 to about 0.1% Si, 0 to about 0.2% Fe, 0 to about 0.3% Cu, 0 to about 0.5% Mn, 2.0 to about 5.0% Mg, 0 to about 0.2% Cr, 0 to about 0.2% Zn, 0 to about 0.1% Ti, and up to 0.15% impurities, which are processed through direct chill casting or continuous casting, followed by homogenization, hot rolling, cold rolling, and annealing to achieve high strength, excellent anodizing quality, and high formability.

Benefits of technology

The described aluminum alloys exhibit yield strengths of at least about 200 MPa and tensile elongation of about 7% or more, while maintaining excellent anodizing quality and high formability, thus addressing the limitations of existing alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649733000007
    Figure 0007649733000007
  • Figure 0007649733000008
    Figure 0007649733000008
  • Figure 0007649733000009
    Figure 0007649733000009
Patent Text Reader

Abstract

Anodized quality aluminum alloys having high strength and high formability, products containing the aluminum alloys, and methods for producing the same are provided. [Solution] Anodized quality AA5xxx series aluminum alloys are provided, containing 0.01-0.1 wt% Si, 0-0.2 wt% Fe, 0-0.3 wt% Cu, 0.13 wt% to less than 0.5 wt% Mn, 3.0-4.0 wt% Mg, 0.001-0.2 wt% Cr, 0-0.2 wt% Zn, 0-0.1 wt% Ti, and up to 0.15 wt% impurities, with the remainder being Al.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Application No. 62 / 481,796, filed April 5, 2017, the disclosure of which is incorporated herein by reference in its entirety.

[0002] The present disclosure relates to aluminum alloy products, and more particularly, to aluminum alloy sheet exhibiting high strength and formability. [Background technology]

[0003] Anodizing quality 5xxx series aluminum alloys currently in use typically have yield strengths in the range of 170MPa to 190MPa. Products made from these alloys are susceptible to mechanical damage. For example, mobile phones made from these alloys are easily scratched, dented, or bent when subjected to external forces (such as impacts on the floor). Attempts to increase strength generally result in a deterioration of anodizing quality. Summary of the Invention

[0004] Exhaustive embodiments of the present invention are defined by the claims, not this Summary of the Invention. This Summary is a high-level overview of various aspects of the present invention and introduces some of the concepts that are further described in the Detailed Description section below. This Summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used alone to determine the scope of the claimed subject matter. The subject matter should be understood by reference to the entire specification, any or all drawings, and appropriate portions of each claim.

[0005] Described herein is an anodized quality aluminum alloy having high strength and high formability, and a method for making the same. The aluminum alloy described herein contains 0 to about 0.1 wt.% Si, 0 to about 0.2 wt.% Fe, 0 to about 0.3 wt.% Cu, 0 to about 0.5 wt.% Mn, about 2.0 to about 5.0 wt.% Mg, 0 to about 0.2 wt.% Cr, 0 to about 0.2 wt.% Zn, 0 to about 0.1 wt.% Ti, and up to 0.15 wt.% impurities, the balance being Al. In some cases, the aluminum alloy contains 0 to about 0.05 wt.% Si, 0 to about 0.1 wt.% Fe, 0 to about 0.1 wt.% Cu, about 0.2 to about 0.5 wt.% Mn, about 2.0 to about 4.5 wt.% Mg, 0 to about 0.1 wt.% Cr, 0 to about 0.1 wt.% Zn, 0 to about 0.05 wt.% Ti, and up to 0.15 wt.% impurities, the balance being Al. In some cases, the aluminum alloy comprises about 0.01 to about 0.05 wt.% Si, about 0.01 to about 0.08 wt.% Fe, about 0.01 to about 0.05 wt.% Cu, about 0.4 to about 0.5 wt.% Mn, about 3.0 to about 4.0 wt.% Mg, about 0.001 to about 0.05 wt.% Cr, about 0.001 to about 0.05 wt.% Zn, about 0.001 to about 0.03 wt.% Ti, and up to 0.15 wt.% impurities, with the balance being Al. Optionally, the aluminum alloy is produced by direct chill casting or continuous casting. The aluminum alloy may be processed by homogenization, hot rolling, cold rolling, and / or annealing.

[0006] Also described herein are products that include the aluminum alloys described above. The product may be, for example, a sheet. In some examples, the sheet includes an anodized sheet. In some cases, one or more surfaces of the anodized sheet have a 60° gloss value of 60 to 100. In some cases, one or more surfaces of the anodized sheet have an L value of 60 to 90, an a value of -2 to 2, and / or an ab value of -2 to 2, respectively, as measured by the Hunter L, a, b color scale. Optionally, one or more surfaces of the sheet have a surface roughness value of 0.1 μm to 0.35 μm. Optionally, one or more surfaces of the anodized sheet have a surface roughness value of 0.2 μm to 0.8 μm. In some cases, one or more surfaces of the anodized sheet have a 60° gloss value of 60 to 100, an L value of 60 to 90, an a value of -2 to 2, and / or an ab value of -2 to 2, respectively, as measured by the Hunter L, a, b color scale. 2 ) or less, the defects including razor leak defects or pick up point defects.

[0007] The sheet may have a yield strength of at least about 200 MPa (e.g., from about 200 MPa to about 350 MPa). The sheet may also have a tensile elongation of about 7% or greater. Optionally, the product includes a consumer electronics component, a consumer appliance component, a building sheet product, a building sheet product component, or an automotive body component, among others.

[0008] Further described herein is a method for producing an aluminum product. The method for producing an aluminum product includes casting an aluminum alloy described herein to form a cast aluminum alloy, scalping the cast aluminum alloy, homogenizing the cast aluminum alloy, hot rolling the cast aluminum alloy to produce a rolled product, and cold rolling the rolled product. Optionally, the cold rolling step is a two-stage cold rolling step. The two-stage cold rolling step may include a first cold rolling step, an intermediate annealing step, and a second cold rolling step. Optionally, the method may further include annealing the rolled product after the cold rolling step. Also described is an aluminum alloy product made by the method described herein.

[0009] Further aspects, objects, and advantages will become apparent from a consideration of the following detailed description of non-limiting examples. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic diagram of processing conditions for sheets made from aluminum alloys as described herein. [Figure 2A] 1 is a photograph of the surface of Comparative Alloy A described herein. [Figure 2B] 1 is a photograph of the surface of an exemplary alloy 1 described herein. [Diagram 3] 1 is a graph showing gloss units at 60° for the top and bottom surfaces of Comparative Alloy A and Alloy 1. [Figure 4A] 1 is a photograph of the surface of an exemplary alloy 1 described herein. [Figure 4B] 1 is a photograph of the surface of Comparative Alloy B described herein. [Diagram 5] 1 is a graph showing gloss units at 60° for the surfaces of Comparative Alloy B and Exemplary Alloy 1 described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Described herein are anodized quality aluminum alloys and alloy products having high strength and high formability, and methods for their manufacture. The alloy products described herein exhibit yield strengths approximately 20%-30% higher than products made from aluminum alloys having comparable levels of anodized quality and formability. Strength is increased by adding strengthening elements that improve strength while maintaining anodized quality and formability. Achieving high strength, high formability, and excellent anodized quality characteristics is unexpected, especially since previous efforts to increase strength have failed because strengthening elements significantly degraded anodized quality. As described herein, the amounts of certain elements are carefully balanced so that high strength, excellent anodized quality, and high formability are obtained simultaneously. The alloys described herein may be used in electronics, transportation, construction, industrial, automotive, and other applications.

[0012] Definitions and Explanations: The terms "invention," "the invention," "this invention," and "the present invention" as used herein are intended to refer broadly to all of the subject matter of this patent application and the claims that follow. Statements containing these terms are to be understood in no way to limit the subject matter described herein or to limit the meaning or scope of the claims that follow.

[0013] In this description, reference is made to alloys identified by aluminum industry designations such as "series" or "5xxx." For an understanding of the number designation systems most commonly used in naming and identifying aluminum and its alloys, reference is made to "International Alloy Designations and Chemical Composition Limits for Wrought Aluminum and Wrought Aluminum Alloys" or "Registration Record of Aluminum Association Alloy Designations and Chemical Compositions Limits for Aluminum Alloys in the Form of Castings and Ingot," both published by The Aluminum Association.

[0014] As used herein, the meanings of "a," "an," or "the" include singular and plural references unless the context clearly dictates otherwise.

[0015] As used herein, plate generally has a thickness of greater than about 15 mm. For example, plate may refer to an aluminum product having a thickness of greater than about 15 mm, greater than about 20 mm, greater than about 25 mm, greater than about 30 mm, greater than about 35 mm, greater than about 40 mm, greater than about 45 mm, greater than about 50 mm, or greater than about 100 mm.

[0016] As used herein, a shade (also referred to as a sheet plate) generally has a thickness of about 4 mm to about 15 mm. For example, the shade may have a thickness of about 4 mm, about 5 mm, about 6 mm, about 7 mm, about 8 mm, about 9 mm, about 10 mm, about 11 mm, about 12 mm, about 13 mm, about 14 mm, or about 15 mm.

[0017] As used herein, "sheet" generally refers to an aluminum product having a thickness of less than about 4 mm. For example, the sheet may have a thickness of less than about 4 mm, less than about 3 mm, less than about 2 mm, less than about 1 mm, less than about 0.5 mm, less than about 0.3 mm, or less than about 0.1 mm.

[0018] As used herein, the term foil refers to an alloy thickness in the range of up to about 0.2 mm (i.e., 200 microns (μm)). For example, the foil may have a thickness of 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, or up to 200 μm.

[0019] In this application, reference is made to the alloy temper or state. For an understanding of the most commonly used alloy temper descriptions, please refer to "American National Standards (ANSI) H35 on Alloy and Temper Designation Systems". Hxx condition or temper, also referred to herein as H temper, refers to the aluminum alloy after cold rolling with or without heat treatment (e.g., annealing). Suitable H tempers include HX1, HX2, HX3, HX4, HX5, HX6, HX7, HX8, or HX9 tempers. For example, the aluminum alloy can be only cold rolled to provide a possible H19 temper. In a further example, the aluminum alloy can be cold rolled and annealed to provide a possible H23 temper.

[0020] As used herein, the meaning of "room temperature" can include temperatures from about 15°C to about 30°C, such as about 15°C, about 16°C, about 17°C, about 18°C, about 19°C, about 20°C, about 21°C, about 22°C, about 23°C, about 24°C, about 25°C, about 26°C, about 27°C, about 28°C, about 29°C, or about 30°C.

[0021] As used herein, the terms "cast metal product," "cast product," "cast aluminum alloy," "cast aluminum alloy product," and the like are used interchangeably and refer to products produced by direct chill casting (including direct chill co-casting) or semi-continuous casting, continuous casting (including, for example, by using a twin belt caster, twin roll caster, block caster, or any other continuous casting machine), electromagnetic casting, hot top casting, or any other casting method.

[0022] All ranges disclosed herein are understood to encompass any and all subranges subsumed therein. For example, a range stated as "1 to 10" should be considered to include any and all subranges between (and including) the minimum value of 1 and the maximum value of 10, i.e., all subranges beginning at or above a minimum value of 1, e.g., 1 to 6.1, and ending at or below a maximum value of 10, e.g., 5.5 to 10.

[0023] The following aluminum alloys are listed with respect to their elemental composition in weight percentages (wt.%) based on the total weight of the alloy. In the specific example of each alloy, the balance is aluminum, with a maximum wt.% of 0.15% for the sum of impurities.

[0024] Alloy composition The novel aluminum-containing 5xxx series alloys are described below. The alloy products made from the alloys exhibit high strength, excellent anodization quality, and high formability. The properties of the alloy products made from the alloys described herein are achieved by the elemental composition of the alloys and the processing method of the alloys, as further described below. In particular, Si, Cu, and Fe are carefully controlled and included or excluded in combination with Mg, Mn, and / or other elements, as further described below, to achieve high strength alloys that maintain excellent anodization quality. Such a design is surprising, since it has been the understanding in the industry that alloys with excellent anodization quality have limited strength.

[0025] In some examples, the alloy may have the following elemental composition as provided in Table 1. [Table 1]

[0026] In some examples, the alloy may have the following elemental composition as provided in Table 2. [Table 2]

[0027] In some examples, the alloy may have the following elemental composition as provided in Table 3. [Table 3]

[0028] In some examples, the alloys described herein include silicon (Si) in an amount between 0% and about 0.1% (e.g., between about 0.001% and about 0.10%, between 0% and about 0.05%, between about 0.005% and about 0.05%, between about 0.01% and about 0.05%, or between about 0.01% and about 0.03%) based on the total weight of the alloy. For example, the alloy may contain about 0.001%, about 0.002%, about 0.003%, about 0.004%, about 0.005%, about 0.006%, about 0.007%, about 0.008%, about 0.009%, about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, or about 0.10% Si. In some cases, no Si is present in the alloy (i.e., 0%). All expressed in weight percent.

[0029] In some examples, the alloys described herein include iron (Fe) in an amount between 0% and about 0.2% (e.g., between about 0.001% and about 0.2%, between 0 and about 0.1%, between about 0.005% and about 0.1%, between 0.01% and about 0.08%, or between about 0.01% and about 0.05%) based on the total weight of the alloy. For example, the alloy may contain about 0.001%, about 0.002%, about 0.003%, about 0.004%, about 0.005%, about 0.006%, about 0.007%, about 0.008%, about 0.009%, about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.10%, about 0.11%, about 0.12%, about 0.13%, about 0.14%, about 0.15%, about 0.16%, about 0.17%, about 0.18%, about 0.19%, or about 0.20% Fe. In some cases, no Fe is present in the alloy (i.e., 0%). All expressed in weight percent.

[0030] In some examples, the alloys described herein include copper (Cu) in an amount of 0% to about 0.3% (e.g., about 0.001% to about 0.30%, about 0.005% to about 0.2%, 0% to about 0.1%, about 0.01% to about 0.1%, or about 0.01% to about 0.05%) based on the total weight of the alloy. For example, the alloy may include about 0.001%, about 0.002%, about 0.003%, about 0.004%, about 0.005%, about 0.006%, about 0.007%, about 0.008%, about 0.009%, about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.10 ... The alloy may contain about 0.11%, about 0.12%, about 0.13%, about 0.14%, about 0.15%, about 0.16%, about 0.17%, about 0.18%, about 0.19%, about 0.20%, about 0.21%, about 0.22%, about 0.23%, about 0.24%, about 0.25%, about 0.26%, about 0.27%, about 0.28%, about 0.29%, or about 0.30% Cu. In some cases, no Cu is present in the alloy (i.e., 0%). All expressed in weight percent.

[0031] In some examples, the alloys described herein include manganese (Mn) in an amount between 0% and about 0.5% (e.g., between about 0.001% and about 0.5%, between about 0.01% and about 0.3%, between about 0.1% and about 0.2%, between about 0.2% and about 0.5%, between about 0.25% and about 0.5%, between about 0.3% and about 0.5%, or between about 0.4% and about 0.5%) based on the total weight of the alloy. For example, the alloy may be about 0.001%, about 0.002%, about 0.003%, about 0.004%, about 0.005%, about 0.006%, about 0.007%, about 0.008%, about 0.009%, about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.10%, about 0.11%, about 0.12%, about 0.13%, about 0.14%, about 0.15%, about 0.16%, about 0.17%, about 0.18%, about 0.19%, about 0.20%, about 0.21%, about 0.22%, about 0.23%, about 0.24%, about 0.25%, about 0.26%, about 0.27%, about 0.28%, about 0.29%, about 0.30%, about 0.31%, about 0.32%, about 0.33%, about 0.34%, about 0.35%, about 0.36%, about 0.37%, about 0.38%, about 0.39%, about 0.40%, about 0.41%, about 0.42%, about 0.43%, about 0.44%, about 0.45%, about 0.46%, about 0.47%, about 0.48%, about 0.49%, about 0.50%, about 0.51%, about 0.52%, about 0.53%, about 0.54%, about 0.55%, about 0.56%, about 0.57%, about 0.58%, about 0.59%, about 0.60%, about 0.61%, about 0.6 The alloy may contain about 0.21%, about 0.22%, about 0.23%, about 0.24%, about 0.25%, about 0.26%, about 0.27%, about 0.28%, about 0.29%, about 0.30%, about 0.31%, about 0.32%, about 0.33%, about 0.34%, about 0.35%, about 0.36%, about 0.37%, about 0.38%, about 0.39%, about 0.40%, about 0.41%, about 0.42%, about 0.43%, about 0.44%, about 0.45%, about 0.46%, about 0.47%, about 0.48%, about 0.49%, or about 0.50% Mn. In some cases, Mn is absent (i.e., 0%) in the alloy. All expressed in weight percent.

[0032] In some examples, the alloys described herein include magnesium (Mg) in an amount between about 2.0% and about 5.0% (e.g., between about 2.5% and about 4.5%, between about 3.0% and about 4.5%, or between about 3.5% and about 4.0%) based on the total weight of the alloy. In some examples, the alloy may include about 2.0%, about 2.1%, about 2.2%, about 2.3%, about 2.4%, about 2.5%, about 2.6%, about 2.7%, about 2.8%, about 2.9%, about 3.0%, about 3.1%, about 3.2%, about 3.3%, about 3.4%, about 3.5%, about 3.6%, about 3.7%, about 3.8%, about 3.9%, about 4.0%, about 4.1%, about 4.2%, about 4.3%, about 4.4%, about 4.5%, about 4.6%, about 4.7%, about 4.8%, about 4.9%, or about 5.0% Mg, all expressed by weight.

[0033] In some examples, the alloys described herein include chromium (Cr) in an amount between 0% and about 0.2% (e.g., between about 0.001% and about 0.20%, between 0% and about 0.1%, between about 0.005% and about 0.1%, or between about 0.001% and about 0.05%) based on the total weight of the alloy. For example, the alloy may contain about 0.001%, about 0.002%, about 0.003%, about 0.004%, about 0.005%, about 0.006%, about 0.007%, about 0.008%, about 0.009%, about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.10%, about 0.11%, about 0.12%, about 0.13%, about 0.14%, about 0.15%, about 0.16%, about 0.17%, about 0.18%, about 0.19%, or about 0.20% Cr. In some cases, Cr is absent (i.e., 0%) in the alloy. All expressed in weight percent.

[0034] In some examples, the alloys described herein include zinc (Zn) in an amount between 0% and about 0.2% (e.g., between about 0.001% and about 0.20%, between 0% and about 0.1%, between about 0.001% and about 0.05%, between about 0.005% and about 0.1%, or between about 0.01% and about 0.05%) based on the total weight of the alloy. For example, the alloy may contain about 0.001%, about 0.002%, about 0.003%, about 0.004%, about 0.005%, about 0.006%, about 0.007%, about 0.008%, about 0.009%, about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.10%, about 0.11%, about 0.12%, about 0.13%, about 0.14%, about 0.15%, about 0.16%, about 0.17%, about 0.18%, about 0.19%, or about 0.20% Zn. In some cases, Zn is absent (i.e., 0%) in the alloy. All expressed in weight percent.

[0035] In some examples, the alloys described herein include titanium (Ti) in an amount between 0% and about 0.10% (e.g., between about 0.001% and about 0.10%, between 0% and about 0.05%, between about 0.001% and about 0.03%, between about 0.005% and about 0.05%, or between about 0.01% and about 0.03%) based on the total weight of the alloy. For example, the alloy may contain about 0.001%, about 0.002%, about 0.003%, about 0.004%, about 0.005%, about 0.006%, about 0.007%, about 0.008%, about 0.009%, about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, or about 0.10% Ti. In some cases, Ti is absent (i.e., 0%) in the alloy. All expressed in weight percent.

[0036] Optionally, the alloy compositions described herein may further include other trace elements, sometimes referred to as impurities, in amounts of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less, respectively. These impurities include, but are not limited to, V, Zr, Ni, Sn, Ga, Ca, or combinations thereof. Thus, V, Zr, Ni, Sn, Ga, or Ca may be present in the alloy in amounts of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. In some cases, the sum of all impurities does not exceed 0.15% (e.g., 0.10%). All expressed in weight percent. The remaining percentage of the alloy is aluminum.

[0037] In some examples, the alloys described herein have a beta phase composition of Al(Fe,Mn)2Si2 particles. The average composition of the Al(Fe,Mn)2Si2 particles may be about 0.5% to about 0.8% Fe, about 1.2% to about 1.7% Mn, and about 2.0% to about 2.7% Si, with the remainder being Al, all based on the weight of the Al(Fe,Mn)2Si2 particles.

[0038] In some cases, the amount of Fe in the Al(Fe,Mn)2Si2 particles may be from about 0.5% to about 0.75%, from about 0.55% to about 0.70%, or from about 0.60% to about 0.70%. For example, the amount of Fe in the Al(Fe,Mn)2Si2 particles may be about 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, or 0.80%.

[0039] The amount of Mn in the Al(Fe,Mn)2Si2 particles may be about 1.3% to about 1.7%, about 1.4% to about 1.65%, or about 1.5% to about 1.6%. For example, the amount of Mn in the Al(Fe,Mn)2Si2 particles may be about 1.3%, 1.31%, 1.32%, 1.33%, 1.34%, 1.35%, 1.36%, 1.37%, 1.38%, 1.39%, 1.40%, 1.41%, 1.42%, 1.43%, 1.44%, 1.45%, 1.46%, 1.47%, 1.48%, It may be 1.49%, 1.50%, 1.51%, 1.52%, 1.53%, 1.54%, 1.55%, 1.56%, 1.57%, 1.58%, 1.59%, 1.60%, 1.61%, 1.62%, 1.63%, 1.64%, 1.65%, 1.66%, 1.67%, 1.68%, 1.69%, or 1.70%.

[0040] The amount of Si in the Al(Fe,Mn)2Si2 particles may be about 2.1% to about 2.7%, about 2.2% to about 2.6%, or about 2.4% to about 2.6%. For example, the amount of Si in Al(Fe,Mn)2Si2 particles is about 2.10%, 2.11%, 2.12%, 2.13%, 2.14%, 2.15%, 2.16%, 2.17%, 2.18%, 2.19%, 2.20%, 2.21%, 2.22%, 2.23%, 2.24%, 2.25%, 2.26%, 2.27%, 2.28%, 2.29%, 2.30%, 2.31%, 2.32%, 2.33%, 2.34%, 2.35%, 2.36%, 2.37%, 2.38%, and It may be 2.39%, 2.40%, 2.41%, 2.42%, 2.43%, 2.44%, 2.45%, 2.46%, 2.47%, 2.48%, 2.49%, 2.50%, 2.51%, 2.52%, 2.53%, 2.54%, 2.55%, 2.56%, 2.57%, 2.58%, 2.59%, 2.60%, 2.61%, 2.62%, 2.63%, 2.64%, 2.65%, 2.66%, 2.67%, 2.68%, 2.69%, or 2.70%.

[0041] The phase fraction of the Al(Fe,Mn)2Si2 particles in the alloy may be in the range of about 0.2% to about 1% (e.g., about 0.2% to about 0.8% or about 0.3% to about 0.6%). For example, the phase fraction of the Al(Fe,Mn)2Si2 particles in the alloy may be about 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1.0%.

[0042] The average particle size of the Al(Fe,Mn)2Si2 particles in the alloy is approximately 2.0 μm. 2 ~about 5.0μm 2 (For example, about 2.5 μm 2 ~ approx. 4.5 μm 2 or about 3.0 μm 2 ~about 4.0μm 2 For example, the surface area of ​​an Al(Fe,Mn)2Si2 particle in the alloy may be in the range of about 2.0 μm 2 , 2.1 μm 2 , 2.2 μm 2 , 2.3 μm 2 , 2.4 μm 2 , 2.5μm 2 , 2.6 μm 2 , 2.7 μm 2 , 2.8μm 2 , 2.9 μm 2 , 3.0μm 2 , 3.1 μm 2 , 3.2 μm 2 , 3.3 μm 2 , 3.4 μm 2 , 3.5μm 2 , 3.6 μm 2 , 3.7 μm 2 , 3.8 μm 2 , 3.9 μm 2 , 4.0μm 2 , 4.1 μm 2 , 4.2 μm 2 , 4.3 μm 2 , 4.4μm 2 , 4.5μm 2 , 4.6 μm 2 , 4.7μm 2 , 4.8μm 2 , 4.9 μm 2, or 5.0 μm 2 may be also possible.

[0043] The Al(Fe,Mn)2Si2 particles in the alloy may have an average length in the range of about 1.0 μm to about 5.0 μm (e.g., about 1.5 μm to about 4.0 μm or about 2.0 μm to about 3.5 μm). For example, the average length of the Al(Fe,Mn)2Si2 particles in the alloy may be about 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm, 3.1 μm, 3.2 ... m, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm, 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm, or 5.0 μm.

[0044] The Al(Fe,Mn)2Si2 particles in the alloy may have, on average, a low aspect ratio (e.g., width to height ratio). In some cases, a low aspect ratio as described herein is a ratio of about 3 or less (e.g., about 2.5 or less or about 2 or less). For example, the average aspect ratio may be about 3.0 or less, about 2.9 or less, about 2.8 or less, about 2.7 or less, about 2.6 or less, about 2.5 or less, about 2.4 or less, about 2.3 or less, about 2.2 or less, about 2.1 or less, about 2.0 or less, about 1.9 or less, about 1.8 or less, or about 1.7 or less. In some examples, the average aspect ratio may be about 1.0 to about 3.0, about 1.2 to about 2.8, or about 1.5 to about 2.5.

[0045] Alloy properties Products made from the aluminum alloys described herein have a combination of desirable properties including high strength, high anodizing quality, and high formability. The sheet can be provided under a variety of temper conditions, including Hxx temper conditions. Under these temper conditions, the aluminum alloy products can exhibit a yield strength of at least about 200 MPa (e.g., from about 200 MPa to about 350 MPa, from about 210 MPa to about 320 MPa, or from about 230 MPa to about 280 MPa). In non-limiting examples, the yield strength is at least about 210 MPa, at least about 220 MPa, at least about 230 MPa, at least about 240 MPa, at least about 250 MPa, or at least about 260 MPa. For example, the aluminum alloy products described herein may exhibit a yield strength of about 200 MPa, about 210 MPa, about 220 MPa, about 230 MPa, about 240 MPa, about 250 MPa, about 260 MPa, about 270 MPa, about 280 MPa, about 290 MPa, about 300 MPa, about 310 MPa, about 320 MPa, about 330 MPa, about 340 MPa, or about 350 MPa.

[0046] The aluminum alloy products may also exhibit a tensile elongation of about 7% or greater (e.g., about 7.5% to about 15%, about 9% to about 14%, or about 10% to about 13%). In non-limiting examples, the aluminum alloy products described herein may exhibit a tensile elongation of about 7.5% or greater, about 8% or greater, about 8.5% or greater, about 9% or greater, about 9.5% or greater, about 10% or greater, about 10.5% or greater, about 11% or greater, about 11.5% or greater, or about 12% or greater. For example, the aluminum alloy products described herein may exhibit a tensile elongation of about 7%, about 7.5%, about 8%, about 8.5%, about 9%, about 9.5%, about 10%, about 10.5%, about 11%, about 11.5%, about 12%, about 12.5%, about 13%, about 13.5%, about 14%, about 14.5%, or about 15%.

[0047] The aluminum alloy products described herein can be anodized to form an anodized aluminum alloy product. The anodized aluminum alloy product can exhibit a gloss value measured at 60 degrees to the rolling direction (i.e., 60° gloss value) of about 60 to about 100. The 60° gloss value indicates the degree of shine of a surface and can be measured with a glossmeter according to ASTM D523. In some cases, the 60° gloss value can be about 60 or more, about 65 or more, about 70 or more, about 75 or more, about 80 or more, about 85 or more, about 90 or more, or about 95 or more. For example, the 60° gloss value can be about 60, 65, 70, 75, 80, 85, 90, 95, 96, 97, 98, or 99, 100, or any value therebetween.

[0048] The colour of one or more surfaces of the Product shall conform to the Hunter L,a,b Versus CIE 1976 L * a * b * As explained in Application Notes, Insight on Color Vol. 13, No. 2 (2008), it can be quantified by colorimetric measurements using the "Hunter L, a, b" color scale. The Hunter L, a, b, color scale is based on opponent color theory, which assumes that the receptors in the human eye perceive colors as pairs of opposites: light-dark ("L value"), red-green ("a value"), and yellow-blue ("b value").

[0049] The L value refers to the lightness or darkness of the product surface. An L value of 100 indicates the lightest color, and an L value of 0 indicates the darkest color. In some examples, the aluminum alloy products described herein have an L value of about 60 to about 90, as measured on the Hunter L, a, b color scale after the product is anodized. For example, one or more surfaces of an anodized product comprising an aluminum alloy described herein may have an L value of about 65 to about 85 or about 70 to about 80. In some cases, one or more surfaces of an anodized product comprising an aluminum alloy described herein may have an L value of about 60, 65, 70, 75, 80, 85, or 90, or any value therebetween.

[0050] The a-value refers to the redness or greenness of the product surface. A positive a-value refers to a red color of the product surface, while a negative a-value refers to a green color of the product surface. In some examples, the aluminum alloy products described herein have one or more surfaces that have an a-value of about -2 to about 2, as measured on the Hunter L, a, b color scale, after the product is anodized. For example, one or more surfaces of an anodized product comprising an aluminum alloy as described herein can have an a-value of about -2.0, -1.9, -1.8, -1.7, -1.6, -1.5, -1.4, -1.3, -1.2, -1.1, -1.0, -0.9, -0.8, -0.7, -0.6, -0.5, -0.4, -0.3, -0.2, -0.1, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, or any value in between.

[0051] The b-value refers to the yellowness or blueness of the product surface. A positive b-value refers to a yellow color of the product surface, and a negative b-value refers to a blue color of the product surface. In some examples, the aluminum alloy products described herein have one or more surfaces that have a b-value of about -2 to about 5 (e.g., about -2 to about 2) on the Hunter L, a, b color scale after the product is anodized. For example, one or more surfaces of an anodized product comprising an aluminum alloy described herein may have a b-value of about -2.0, -1.9, -1.8, -1.7, -1.6, -1.5, -1.4, -1.3, -1.2, -1.1, -1.0, -0.9, -0.8, -0.7, -0.6, -0.5, -0.4, -0.3, -0.2, -0.1, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.1, 0. ...0, 0.1, 0.0, 0.0, 0.1, 0.0, 0.0, 0.1, 0.0, 0.0, 0.0, 0.1, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0.0, 0 9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, or 5.0.

[0052] Optionally, the as-rolled products described herein (e.g., without anodization) can have a surface roughness value (2D and 3D) ranging from about 0.1 μm to about 0.35 μm (e.g., 0.10 μm, 0.15 μm, 0.20 μm, 0.25 μm, 0.30 μm, or 0.35 μm, or any range therebetween. In some cases, the products described herein can have a surface roughness value (2D and 3D) after anodization ranging from about 0.2 μm to about 0.8 μm (e.g., 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, or 0.80 μm, or any range therebetween).

[0053] In some cases, the anodized aluminum alloy products described herein can be free of or free of nearly all visible defects, such as razor leaks or pick-up point defects after anodization. Razor leaks typically appear as dark or light lines. Pick-up point defects typically appear as dark or light spots. However, the anodized aluminum alloy products described herein have minimized components and minimized elongated grains compared to conventional anodized aluminum alloy products. Additionally, the products described herein are processed to minimize surface oxidation and other contamination, resulting in a smooth rolled surface of the anodized aluminum alloy product. In some examples, one or more surfaces of the anodized aluminum alloy product may have a minimum of 100% of the surface area per square meter (m ) of the product surface. 2 ) or less than one razor leak defect per square meter of the product surface. In some instances, one or more surfaces of an anodized aluminum alloy product may have a razor leak defect per square meter of the product surface. 2 Contains no more than one pick point defect per unit.

[0054] The aluminum alloy products described herein may have any suitable gauge. The alloys described above may be cast and processed into various sizes and thicknesses, such as foils (e.g., less than about 0.20 mm), sheets (e.g., about 0.20 mm to 4.0 mm), shades (e.g., about 4.0 mm to 15.0 mm), or plates (e.g., greater than about 15.0 mm), although other thicknesses and ranges may be used as well. In some examples, the aluminum alloy products described herein may be provided and supplied to a customer or end user in an intermediate gauge (e.g., a gauge that is further reduced by the customer or end user as needed). In some examples, the aluminum alloy products described herein may be provided and supplied to a customer or end user in a final gauge (e.g., a gauge that is not further reduced by the customer or end user).

[0055] Method of preparation In certain embodiments, the disclosed alloy compositions are products of the disclosed methods. Without intending to limit the disclosure, the properties of the aluminum alloy product are determined in part by the formation of the microstructure during fabrication of the alloy product. In certain embodiments, the method of fabrication of the product can affect or even determine whether the resulting alloy has suitable properties for a desired application.

[0056] Minting and Scalping The alloys described herein can be cast into ingots using a direct chill (DC) process or can be cast using a continuous casting (CC) process. The casting process is performed according to standards commonly used in the aluminum industry as known to those skilled in the art. The CC process can include, but is not limited to, the use of a twin belt caster, a twin roll caster, or a block caster. In some examples, the casting process is performed by a CC process to form slabs, strips, etc. In some examples, the casting process is a DC casting process to form cast ingots. Optionally, a molten metal filter (e.g., a ceramic foam filter or a porous tube filter) may be used during the casting process to improve the cleanliness of the metal.

[0057] If formed by DC casting, the cast ingot may then be scalped. Optionally, the ingot may be scalped up to 20 mm per side (e.g., 1 mm per side, 2 mm per side, 5 mm per side, 10 mm per side, 15 mm per side, or 20 mm per side). For example, the cast ingot may be scalped 1 mm to 20 mm per side, 5 mm to 20 mm per side, 10 mm to 20 mm per side, or 15 mm to 20 mm per side.

[0058] The cast product (e.g., ingot, slab, or strip) may be subjected to further processing steps. Optionally, further processing steps may be used to create products such as sheets, plates, or shoots. Such processing steps include, but are not limited to, homogenization, hot rolling, cold rolling, which may optionally include intermediate annealing steps, and an optional final annealing step. Below, the processing steps are described in relation to cast ingots. However, the processing steps can also be used for cast slabs or strips, with modifications as would be recognized by one of ordinary skill in the art.

[0059] Homogenization As noted above, the processing step includes a homogenization step, in which an ingot made from an alloy composition described herein is heated to achieve a peak metal temperature of at least about 475°C (e.g., at least about 480°C, at least about 485°C, at least about 490°C, at least about 495°C, at least about 500°C, at least about 505°C, at least about 510°C, at least about 515°C, at least about 520°C, at least about 525°C, at least about 530°C, at least about 535°C, at least about 540°C, at least about 545°C, or at least about 550°C). In some examples, the ingot is heated to a temperature in the range of about 480°C to about 550°C (e.g., about 490°C to about 540°C or about 500°C to about 550°C). The heating rate to the peak metal temperature may be about 10°C / min to about 100°C / min. For example, the heating rate to the peak metal temperature can be about 10° C. / min, about 20° C. / min, about 30° C. / min, about 40° C. / min, about 50° C. / min, about 60° C. / min, about 70° C. / min, about 80° C. / min, about 90° C. / min, or about 100° C. / min.

[0060] The ingot is then soaked (i.e., held at the indicated temperature) for a period of time. In some cases, the ingot may be soaked for at least 30 minutes at the peak metal temperature as described above. For example, the ingot may be soaked for at least 30 minutes, at least 1 hour, at least 2 hours, at least 3 hours, at least 4 hours, or at least 5 hours.

[0061] Hot rolling and coiling After the homogenization step, a hot rolling step can be performed. The hot rolling step can be performed using a single stand mill or a multi-stand mill, such as a hot reversing mill operation or a hot tandem mill operation. In certain cases, the ingot is placed and hot rolled at an inlet temperature in the range of about 450°C to about 550°C. The inlet temperature can be, for example, about 450°C, about 460°C, about 470°C, about 480°C, about 490°C, about 500°C, about 510°C, about 520°C, about 530°C, about 540°C, or about 550°C. In certain cases, the hot rolling outlet temperature can be in the range of about 250°C to about 350°C. The exit temperature may be, for example, about 250°C, about 260°C, about 270°C, about 280°C, about 290°C, about 300°C, about 310°C, about 320°C, about 330°C, about 340°C, or about 350°C. The ingot can then be hot rolled to a thickness of 12 mm gauge or less. For example, the ingot can be hot rolled to a thickness of 11 mm gauge or less, a thickness of 10 mm gauge or less, a thickness of 9 mm gauge or less, a thickness of 8 mm gauge or less, a thickness of 7 mm gauge or less, a thickness of 6 mm gauge or less, a thickness of 5 mm gauge or less, a thickness of 4 mm gauge or less, a thickness of 3 mm gauge or less, a thickness of 2 mm gauge or less, or a thickness of 1 mm gauge or less.

[0062] At the end of the hot rolling step, the sheet can be wound into a coil, optionally in a single stand or multi-stand mill, at a coiling temperature ranging from about 285° C. to about 350° C. (e.g., from about 300° C. to about 350° C. or from about 310° C. to about 330° C.).

[0063] Cold rolling and annealing The hot rolled coil, plate, shade, or sheet can then undergo a cold rolling step to form a cold rolled coil, sheet, or shade. The cold rolling step can be performed using a single stand mill or a multi-stand mill. In some cases, the cold rolling step is a one-stage cold rolling process. In some cases, the cold rolling step is a two-stage cold rolling process.

[0064] In a one-stage cold rolling process, the temperature of the coil or sheet can be reduced to a temperature in the range of about 20°C to about 150°C (e.g., about 25°C to about 140°C or about 40°C to about 120°C). In some cases, the coil or sheet is cold rolled at an entry temperature in the range of about 20°C to about 150°C (e.g., about 25°C to about 140°C or about 40°C to about 120°C). The entry temperature can be, for example, about 20°C, about 30°C, about 40°C, about 50°C, about 60°C, about 70°C, about 80°C, about 90°C, about 100°C, about 110°C, about 120°C, about 130°C, about 140°C, or about 150°C. In some cases, the cold rolling exit temperature may be in the range of about 80°C to about 200°C (e.g., about 100°C to about 190°C or about 110°C to about 180°C). The exit temperature may be, for example, about 80°C, about 90°C, about 100°C, about 110°C, about 120°C, about 130°C, about 140°C, about 150°C, about 160°C, about 170°C, about 180°C, about 190°C, or about 200°C.

[0065] The cold rolling step may be carried out at a temperature suitable for cold rolling as described above for a period of time resulting in a gauge of about 0.2 mm to about 5 mm. For example, the resulting gauge may be about 0.5 mm to about 4 mm, about 0.8 mm to about 3.5 mm, about 1 mm to about 3 mm, or about 1.45 mm to about 2 mm. Optionally, the cold rolling step may be carried out for a period of up to about 1 hour (e.g., about 10 minutes to about 30 minutes). For example, the cold rolling step may be carried out for a period of about 10 minutes, about 20 minutes, about 30 minutes, about 40 minutes, about 50 minutes, or about 1 hour.

[0066] As mentioned above, the cold rolling step may be a two-stage cold rolling process in which an intermediate annealing step is performed during cold rolling. In a two-stage cold rolling process, the temperature of the coil or sheet may be reduced to a temperature in the range of about 20°C to about 150°C (e.g., about 25°C to about 140°C or about 40°C to about 120°C). In some cases, the coil or sheet is cold rolled at an inlet temperature in the range of about 20°C to about 150°C. The inlet temperature may be, for example, about 20°C, about 30°C, about 40°C, about 50°C, about 60°C, about 70°C, about 80°C, about 90°C, about 100°C, about 110°C, about 120°C, about 130°C, about 140°C, or about 150°C. In some cases, the cold rolling outlet temperature may be in the range of about 80°C to about 200°C. The outlet temperature can be, for example, about 80°C, about 90°C, about 100°C, about 110°C, about 120°C, about 130°C, about 140°C, about 150°C, about 160°C, about 170°C, about 180°C, about 190°C, or about 200°C.

[0067] The first stage of the cold rolling step may be carried out at a temperature suitable for cold rolling as described above for a period of time resulting in a gauge of about 1.2 mm to about 5 mm. For example, the resulting gauge may be about 1.25 mm to about 4 mm, about 1.3 mm to about 3.5 mm, about 1.4 mm to about 3 mm, or about 1.45 mm to about 2 mm. Optionally, the cold rolling step may be carried out for a period of up to about 1 hour (e.g., about 10 minutes to about 30 minutes). For example, the cold rolling step may be carried out for a period of about 10 minutes, about 20 minutes, about 30 minutes, about 40 minutes, about 50 minutes, or about 1 hour.

[0068] The next step in the two-stage cold rolling process may be an annealing process, referred to herein as an intermediate annealing step. In the intermediate annealing step, the cold rolled product may be held at a temperature in the range of about 250°C to about 400°C (e.g., about 275°C to about 375°C or about 300°C to about 350°C) for a soaking time of up to about 4 hours. For example, the soaking time may be in the range of about 10 minutes to about 4 hours (e.g., about 10 minutes, about 30 minutes, about 1 hour, about 2 hours, about 3 hours, or about 4 hours). Optionally, the intermediate annealing step may result in an alloy product having rounded grains. In some cases, at least about 50% of the grains present in the alloy product are round (e.g., at least about 60%, at least about 70%, at least about 80%, or at least about 90% of the grains in the alloy product are round).

[0069] Following the intermediate annealing step, a second stage of the cold rolling process can be performed. In some cases, the second stage of the cold rolling process includes cold rolling using a single stand mill or a multi-stand mill with an inlet temperature ranging from about 20°C to about 150°C. The inlet temperature can be, for example, about 20°C, about 30°C, about 40°C, about 50°C, about 60°C, about 70°C, about 80°C, about 90°C, about 100°C, about 110°C, about 120°C, about 130°C, about 140°C, or about 150°C. In some cases, the cold rolling outlet temperature can range from about 80°C to about 200°C. The outlet temperature may be, for example, about 80° C., about 90° C., about 100° C., about 110° C., about 120° C., about 130° C., about 140° C., about 150° C., about 160° C., about 170° C., about 180° C., about 190° C., or about 200° C. to obtain a gauge of about 2 mm or less (e.g., about 0.2 mm to about 2 mm or about 0.2 mm to about 1.4 mm). For example, the resulting gauge may be about 0.2 mm, about 0.3 mm, about 0.4 mm, about 0.5 mm, about 0.6 mm, about 0.7 mm, about 0.8 mm, about 0.9 mm, about 1 mm, about 1.1 mm, about 1.2 mm, about 1.3 mm, about 1.4 mm, about 1.5 mm, about 1.6 mm, about 1.7 mm, about 1.8 mm, about 1.9 mm, or about 2 mm.

[0070] Optionally, the rolled product may then be subjected to an annealing process, also referred to herein as a stabilization annealing step, at a temperature of about 100° C. to about 250° C. (e.g., about 125° C. to about 200° C. or about 135° C. to about 175° C.) with a soaking time of up to about 4 hours. For example, the soaking time may range from about 10 minutes to about 4 hours (e.g., about 10 minutes, about 20 minutes, about 30 minutes, about 40 minutes, about 50 minutes, about 1 hour, about 2 hours, about 3 hours, or about 4 hours).

[0071] After annealing, the rolled product may optionally be subjected to one or more additional steps including tension leveling and / or packaging.

[0072] How to use The products and methods described herein can be used in electronics, transportation (such as automobiles), construction, and industrial applications, among others. In some cases, the sheets can be used in Hxx tempers for applications requiring alloys with high formability. In some cases, the sheets can be used to make products such as consumer electronics or consumer electronics parts. Exemplary consumer electronics include mobile phones, audio devices, video devices, cameras, laptop computers, desktop computers, tablet computers, televisions, displays, home appliances, video playback and recording devices, and the like. Exemplary consumer electronics parts include exterior housings (e.g., facades) and interior parts for consumer electronics parts. The sheets can be used, for example, as housings for mobile phones and tablet computers, and as electronic interior chassis. In some cases, the sheets can be used to make architectural sheet products and architectural sheet product parts. In some examples, the sheets and methods described herein can be used to make automotive body parts, such as inner panels. In some cases, the sheets and methods described herein can be used to tailor luggage (such as suitcases).

[0073] Examples of suitable products and methods As used hereinafter, any reference to a series of examples should be understood as a reference to each of those examples in isolation (e.g., "Examples 1-4" should be understood as "Examples 1, 2, 3, or 4").

[0074] Example 1 is an aluminum alloy containing 0 to about 0.1 wt.% Si, 0 to about 0.2 wt.% Fe, 0 to about 0.3 wt.% Cu, 0 to about 0.5 wt.% Mn, about 2.0 to about 5.0 wt.% Mg, 0 to about 0.2 wt.% Cr, 0 to about 0.2 wt.% Zn, 0 to about 0.1 wt.% Ti, and up to 0.15 wt.% impurities, balance Al.

[0075] Example 2 is an aluminum alloy of any of the preceding or subsequent examples containing 0 to about 0.05 wt. % Si, 0 to about 0.1 wt. % Fe, 0 to about 0.1 wt. % Cu, about 0.2 to about 0.5 wt. % Mn, about 2.0 to about 4.5 wt. % Mg, 0 to about 0.1 wt. % Cr, 0 to about 0.1 wt. % Zn, 0 to about 0.05 wt. % Ti, and up to 0.15 wt. % impurities, the balance being Al.

[0076] Example 3 is an aluminum alloy of any of the preceding or subsequent examples containing about 0.01 to about 0.05 weight percent Si, about 0.01 to about 0.08 weight percent Fe, about 0.01 to about 0.05 weight percent Cu, about 0.4 to about 0.5 weight percent Mn, about 3.0 to about 4.0 weight percent Mg, about 0.001 to about 0.05 weight percent Cr, about 0.001 to about 0.05 weight percent Zn, about 0.001 to about 0.03 weight percent Ti, and up to 0.15 weight percent impurities, the balance being Al.

[0077] Example 4 is an aluminum alloy of either the preceding or subsequent examples in which the aluminum alloy is produced by direct chill casting.

[0078] Example 5 is an aluminum alloy of either the preceding or subsequent examples, where the aluminum alloy is processed by homogenizing, hot rolling, cold rolling, and annealing.

[0079] Example 6 is a product that includes an aluminum alloy of any of the preceding or subsequent examples.

[0080] Example 7 is a product of either the preceding or succeeding examples that is a sheet.

[0081] Example 8 is the product of any of the preceding or subsequent examples in which the sheet is an anodized sheet.

[0082] Example 9 is a product of any of the preceding or subsequent examples, in which one or more surfaces of the anodized sheet have a 60° gloss value of 60-100.

[0083] Example 10 is the product of any of the preceding or subsequent examples, wherein one or more surfaces of the anodized sheet have an L value of 60 to 90 as measured by the Hunter L, a, b color scale.

[0084] Example 11 is a product of any of the preceding or subsequent examples, in which one or more surfaces of the anodized sheet have an a value of -2 to 2 as measured by the Hunter L, a, b color scale.

[0085] Example 12 is the product of any of the preceding or subsequent examples, in which one or more surfaces of the anodized sheet have a b value of -2 to 2 as measured by the Hunter L, a, b color scale.

[0086] Example 13 is the product of any of the preceding or subsequent examples, where one or more surfaces of the sheet have a surface roughness value between 0.1 μm and 0.35 μm.

[0087] Example 14 is the product of any of the preceding or subsequent examples, where one or more surfaces of the anodized sheet have a surface roughness value of between 0.2 μm and 0.8 μm.

[0088] Example 15 shows a case where one or more surfaces of the anodized sheet are oxidized over a square meter (m 2) or less, the defects being products of either the preceding or succeeding examples, including razor leak defects or pick-up point defects.

[0089] Example 16 is a product of any of the preceding or subsequent examples in which the sheet has a yield strength of at least about 200 MPa.

[0090] Example 17 is a product of either the preceding or subsequent examples in which the sheet has a yield strength of about 200 MPa to about 350 MPa.

[0091] Example 18 is a product of any of the preceding or subsequent examples in which the sheet has a tensile elongation of about 7% or greater.

[0092] Example 19 is a product of any of the preceding or subsequent examples that includes a consumer electronic part or consumer appliance part.

[0093] Example 20 is a product of any of the preceding or subsequent examples that includes a building sheet product or a building sheet product component.

[0094] Example 21 is a product of either the preceding or succeeding examples that includes an automobile body part.

[0095] Example 22 is a method for producing an aluminum product, the method including: casting an aluminum alloy to form a cast aluminum alloy, the aluminum alloy containing 0 to about 0.1 wt. % Si, 0 to about 0.2 wt. % Fe, 0 to about 0.3 wt. % Cu, 0 to about 0.5 wt. % Mn, about 2.0 to about 5.0 wt. % Mg, 0 to about 0.2 wt. % Cr, 0 to about 0.2 wt. % Zn, 0 to about 0.1 wt. % Ti, up to 0.15 wt. % impurities, and balance Al; scalping the cast aluminum alloy; homogenizing the cast aluminum alloy; hot rolling the cast aluminum alloy to produce a rolled product; and cold rolling the rolled product.

[0096] Example 23 is the method of any of the preceding or subsequent examples, wherein the aluminum alloy contains 0 to about 0.05 wt.% Si, 0 to about 0.1 wt.% Fe, 0 to about 0.1 wt.% Cu, about 0.2 to about 0.5 wt.% Mn, about 2.0 to about 4.5 wt.% Mg, 0 to about 0.1 wt.% Cr, 0 to about 0.1 wt.% Zn, 0 to about 0.05 wt.% Ti, and up to 0.15 wt.% impurities, the balance being Al.

[0097] Example 24 is the method of any of the preceding or subsequent examples, wherein the aluminum alloy contains about 0.01 to about 0.05 wt. % Si, about 0.01 to about 0.08 wt. % Fe, about 0.01 to about 0.05 wt. % Cu, about 0.4 to about 0.5 wt. % Mn, about 3.0 to about 4.0 wt. % Mg, about 0.001 to about 0.05 wt. % Cr, about 0.001 to about 0.05 wt. % Zn, about 0.001 to about 0.03 wt. % Ti, and up to 0.15 wt. % impurities, the balance being Al.

[0098] Example 25 is the method of any of the preceding or subsequent examples, further comprising annealing the rolled product after the cold rolling step.

[0099] Example 26 is the process of any of the preceding or subsequent examples, wherein the cold rolling step is a two-stage cold rolling step.

[0100] Example 27 is the method of any of the preceding or subsequent examples, where the two-stage cold rolling step includes a first cold rolling step, an intermediate annealing step, and a second cold rolling step.

[0101] Example 28 is an aluminum alloy product made by the method of any of the preceding or succeeding examples.

[0102] The following examples serve to further illustrate the present invention, but do not limit it. On the contrary, it should be clearly understood that after reading the description herein, the present invention can be applied to various embodiments, modifications and equivalents that may suggest themselves to those skilled in the art, without departing from the spirit of the present invention. EXAMPLES

[0103] Example 1 The aluminum alloys described herein, and comparative alloys shown in Table 4, were made according to the methods described herein. Alloy 1 is an exemplary alloy formed according to the methods described herein using the steps shown in FIG. 1. Alloy A is AA5252, currently used in commercial applications as an anodizing quality alloy. Alloy A was made similarly to Alloy 1, but with a final cold rolling reduction of 18% for Alloy A, while Alloy 1 was reduced by 45%. Variations in the cold rolling reduction between the two alloys were introduced to produce comparable samples due to differences in mechanical properties between the compositions. In each alloy, the balance is aluminum, and all values ​​are expressed as weight percent. [Table 4]

[0104] The mechanical properties of the exemplary and comparative alloys were determined, specifically, yield strength and tensile elongation were determined according to ASTM B557, and overhang height limit (indicative of formability) was determined according to ASTM E643. The test results are summarized in Table 5. [Table 5]

[0105] The mechanical properties show that Exemplary Alloy 1 exhibits higher yield strength, higher tensile elongation, and higher formability than Comparative Alloy A.

[0106] The appearance of the exemplary and comparative alloys was also compared. As shown in Figures 2A and 2B, Alloy 1 (Figure 2B) exhibits anodization quality and linearity (measured by streaks) that is equal to or better than Comparative Alloy A (Figure 2A). 60° gloss values ​​were measured for the top ("Top") and bottom ("Bottom") surfaces of sheets of Comparative Alloy A and Exemplary Alloy 1. The results show that Alloy 1 exhibits a gloss level equal to Comparative Alloy A (see Figure 3).

[0107] Example 2 Alloy 1, as set forth in Table 4 and set forth again in Table 6 below, containing small amounts of Si and Fe, was prepared as described above in Example 1 and compared to Alloy B, a conventional 5xxx series anodizing quality alloy with higher amounts of Si and Fe (Table 6). Alloy B was prepared similarly to Alloy 1, but was finally cold rolled to an 18% reduction for Alloy B, while Alloy 1 was reduced by 45%. The variation in cold rolling reduction between the two alloys was introduced to produce comparable specimens due to the differences in mechanical properties between the compositions. In each alloy, the balance is aluminum, and all values ​​are expressed as weight percent. [Table 6]

[0108] A photograph of the surface of Alloy 1 is shown in FIG. 4A, and a photograph of the surface of Alloy B is shown in FIG. 4B. Alloy 1 exhibited excellent uniformity and gloss. The gloss measurements were quantified into 60° gloss values. See FIG. 5. The results show that Alloy 1 exhibits higher gloss than Alloy B.

[0109] All patents, publications, and abstracts cited above are incorporated herein by reference in their entirety. Various embodiments of the invention have been described to accomplish various objects of the invention. It should be recognized that these embodiments are merely illustrative of the principles of the invention. Many modifications and adaptations thereof will be readily apparent to those skilled in the art without departing from the spirit and scope of the invention as defined in the following claims.

Claims

1. % Si, 0-0.2 wt.% Fe, 0-0.3 wt.% Cu, 0.13 to less than 0.5 wt.% Mn, 3.0-4.0 wt.% Mg, 0.001-0.2 wt.% Cr, 0.001-0.2 wt.% Zn, 0-0.1 wt.% Ti, and up to 0.15 wt.% impurities, the balance being Al, each of said impurities being a maximum of 0.05 wt.%, and having a yield strength of at least 200 MPa and a tensile elongation of 7% or greater.

2. 2. The aluminum alloy of claim 1 comprising 0.01-0.05 wt.% Si, 0-0.1 wt.% Fe, 0-0.1 wt.% Cu, 0.2-0.5 wt.% Mn, 3.0-4.0 wt.% Mg, 0.001-0.1 wt.% Cr, 0.001-0.1 wt.% Zn, 0-0.05 wt.% Ti, and up to 0.15 wt.% impurities, the balance being Al.

3. 3. An aluminum alloy according to claim 2 comprising 0.01-0.05 wt.% Si, 0.01-0.08 wt.% Fe, 0.01-0.05 wt.% Cu, 0.4 to less than 0.5 wt.% Mn, 3.0-4.0 wt.% Mg, 0.001-0.05 wt.% Cr, 0.001-0.05 wt.% Zn, 0.001-0.03 wt.% Ti, and up to 0.15 wt.% impurities, the balance being Al.

4. A product comprising the aluminum alloy according to any one of claims 1 to 3.

5. The product of claim 4 , wherein the product is a sheet.

6. 6. The article of claim 5, wherein the sheet is an anodized sheet.

7. 7. The product of claim 5 or 6, wherein the sheet has a yield strength of between 200 MPa and 350 MPa.

8. The product of any one of claims 4 to 7, wherein the product comprises a consumer electronic or appliance part.

9. The article of manufacture of any one of claims 4 to 7, wherein the article comprises a building sheet product or a building sheet product component.

10. The article of manufacture of any one of claims 4 to 7, wherein the article of manufacture comprises an automotive body part.

11. A method for producing an aluminum alloy product, comprising the steps of: % Si, 0-0.2 wt.% Fe, 0-0.3 wt.% Cu, 0.13 to less than 0.5 wt.% Mn, 3.0-4.0 wt.% Mg, 0.001-0.2 wt.% Cr, 0-0.2 wt.% Zn, 0-0.1 wt.% Ti, and up to 0.15 wt.% impurities, balance Al, each of said impurities being at a maximum of 0.05 wt.%; scalping the cast aluminum alloy; homogenizing the cast aluminum alloy; hot rolling the cast aluminum alloy to produce a rolled product; cold rolling the rolled product; annealing the rolled product after the cold rolling step; The aluminum alloy product has a yield strength of at least 200 MPa and a tensile elongation of 7% or greater.

12. A method for producing an aluminum alloy product, comprising the steps of: % Si, 0-0.2 wt.% Fe, 0-0.3 wt.% Cu, 0.13 to less than 0.5 wt.% Mn, 3.0-4.0 wt.% Mg, 0.001-0.2 wt.% Cr, 0-0.2 wt.% Zn, 0-0.1 wt.% Ti, and up to 0.15 wt.% impurities, balance Al, each of said impurities being at a maximum of 0.05 wt.%; scalping the cast aluminum alloy; homogenizing the cast aluminum alloy; hot rolling the cast aluminum alloy to produce a rolled product; cold rolling the rolled product; and annealing the cold rolling. The cold rolling step is a two-stage cold rolling step, the two-stage cold rolling step including a first cold rolling step, an intermediate annealing step, and a second cold rolling step; The aluminum alloy product has a yield strength of at least 200 MPa and a tensile elongation of 7% or greater.

Citation Information

Patent Citations

  • Production of aluminum alloy blank material for laser reflection mirror

    JP1984157235A

  • Substrate for magnetic recording medium

    JP1989189024A

  • Aluminum alloy sheet for disk having excellent plating characteristics

    JP1990159340A

  • METHOD FOR MANUFACTURING SHEET SUITABLE FOR MAKING COMPONENTS OF CAN

    JP1996501604A